Candidate effectors for leaf rust resistance gene Lr28 identified through transcriptome and in-silico analysis - Prasad, Pramod; Jain, Neelu; Chaudhary, Jyoti; Thakur, Rajni Kant; Savadi, Siddanna; Bhardwaj, Subhash Chander; Gangwar, Om Prakash; Lata, Charu; Adhikari, Sneha; Kumar, Subodh; Balyan, Harindra Singh; Gupta, Pushpendra Kumar (Frontiers in Microbiology, 2023)
Puccinia spp. causing rust diseases in wheat and other cereals secrete several specialized effector proteins into host cells. The effector proteins are generally secretory and influence host response to encourage infection. Characterization of these proteins and their interaction with host's R proteins could greatly help to limit crop losses due to diseases. Prediction of effector proteins by combining the transcriptome analysis and multiple in-silico approaches is gaining importance in revealing the pathogenic mechanism. Despite all the progress and success of effectoromics, little is known about the potential effectors secreted by wheat leaf rust fungus (Puccinia triticina, Pt).The present study involved identification of 13 PtPuccinia triticina (Pt) coding sequences Formatted: Superscript Formatted: Font: Italic Formatted: Font color: Black (CDSs), through transcriptome analysis, that were differentially expressed during wheat-leaf rust interaction; and prediction of their effector like features using different in-silico tools. NCBI-BLAST and pathogen-host interaction BLAST (PHI-BLAST) tools were used to annotate and classify these sequences based on their most closely matched counterpart in both the databases.Homology between CDSs and the annotated sequences in the NCBI database ranged from 79% to 94% and with putative effectors of other plant pathogens in PHI-BLAST from 24.46% to 54.35%. Nine of the 13 CDSs had effector-like features according to EffectorP 3.0 (≥0.546 probability of these sequences to be effector). The qRT-PCR expression analysis revealed that the relative expression of all CDSs in compatible interaction (HD2329) was maximum at 11 days post inoculation (dpi) and that in incompatible interactions (HD2329 + Lr28) was maximum at 3 dpi in seven and 9 dpi in five CDSs. These results suggest that six CDSs (>0.8 effector probability as per EffectorP 3.0) could be considered as putative Pt effectors. The molecular docking and MD simulation analysis of these six CDSs suggested that candidate Lr28 protein binds more strongly to candidate effector c14094_g1_i1 to form more stable complex than the remaining five candidate effectors. Further functional characterization of these six CDSscandidate effectors should prove useful for a better understanding of wheat-leaf rust interaction. In turn, this should facilitate effector-based leaf rust resistance breeding in wheat.